Preparation method of an eco-friendly dust stabilizer
Patent Information
- Application Number
- CN202311409585.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-10-27
AI Technical Summary
在这种高温情况下,道路洒水除尘的水分会很快蒸发,效果很不理想;而多数市面上销售的尘土固化剂由于耐高温性较差,在高温下,这类尘土固化剂的除尘成分会逐步发生降解,进而导致尘土固化剂中的成分失效,其成膜性能显著下降,导致其除尘效果大大降低
[0019](1)本发明以膨润土作为填料,且其可与粘附在路面上的酸性气溶胶反应,能有效除去有害物质,同时减小车轮与路面之间的摩擦力到合理的安全范围,对道路具有一定的优化作用。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental protection and dust suppression, specifically to a method for preparing an eco-friendly dust solidification agent. Background Technology
[0002] In recent years, with the rapid development of the economy and industry and the continuous acceleration of urbanization, the number of urban motor vehicles and road traffic has also increased rapidly. The main pollutants generated include dust and various heavy metals such as Cu, Cr, Zn, Pb, Cd, Ni, and Mn that diffuse through dust adsorption. These heavy metals mainly come from the combustion of motor vehicle fuel, wear during braking, and leakage and corrosion of coolant. Dust and the heavy metals it adsorbs will eventually accumulate in road surface deposits under the action of dry and wet sedimentation.
[0003] Domestically and internationally, water spraying is the primary method for suppressing road dust. While simple and convenient, watering results in rapid evaporation and a short duration of action, failing to meet the long-term effectiveness requirements for roads with thick dust accumulation. Wetting agent dust suppression is a dust removal technology developed based on hydraulic dust removal. When a wetting agent dissolves in water, it reduces the surface tension of the water, enhancing its wetting ability and dust suppression effect, making it particularly suitable for hydrophobic, respirable dust. Currently, extensive research has been conducted on dust pollution suppression, achieving some progress. For example, Chinese patent CN106928901A discloses a colorful environmentally friendly dust suppressant and its preparation and application methods, and Chinese patent CN108570308A discloses a method for preparing a waterproof coal dust suppressant. However, existing dust stabilizers are mostly used in coal mines and railway transportation, with fewer eco-friendly dust stabilizers suitable for urban roads. Furthermore, many construction projects, including road and building construction, are carried out primarily in the summer. However, due to the high summer temperatures, the surface temperature can reach 50-65℃ under prolonged strong sunlight. Under such high temperatures, the water used for road dust suppression evaporates quickly, resulting in a less than ideal effect. Furthermore, most commercially available dust curing agents have poor high-temperature resistance; under high temperatures, the dust-suppressing components of these agents gradually degrade, leading to the inactivation of the components and a significant decrease in their film-forming properties, thus greatly reducing their dust-suppressing effect. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing an eco-friendly dust solidification agent.
[0005] The objective of this invention is achieved through the following technical solution: a method for preparing an eco-friendly dust solidification agent, comprising the following steps:
[0006] S1. Preparation of CTS-PA-CMC: Carboxymethyl cellulose is dissolved in a 30-45 wt% sodium hydroxide solution to obtain a CMC-NaOH composite coagulation solution; chitosan is dissolved in a mixed acid solution of phytic acid and acetic acid to remove bubbles, and is slowly added to the CMC-NaOH composite coagulation solution. After standing for 20-40 min, chitosan-phytic acid-carboxymethyl cellulose CTS-PA-CMC is obtained.
[0007] S2.CMC modification: Separately, carboxymethyl cellulose is dissolved in a 2.8-4 wt% polyacrylamide solution to prepare M-carboxymethyl cellulose with a target concentration of 3-4 wt%.
[0008] S3. Acid leaching and crosslinking: Bentonite is acid-leached in nitric acid solution for 2-3 hours. After acid leaching, CMC and DMF are added to the bentonite, followed by HMDI. The reaction is carried out under nitrogen protection for 6-9 hours to obtain BT-g-CMC. BT-g-CMC is added dropwise to ferric chloride solution to form a hydrogel, resulting in a white viscous paste-like intermediate.
[0009] S4. Mixing: After mixing and stirring the antifreeze, anionic surfactant, and superabsorbent resin, add the M-carboxymethyl cellulose prepared in step S2 and disperse it evenly to obtain a suspension mother liquor; add the CTS-PA-CMC prepared in step S1 and the white viscous paste intermediate prepared in step S3 to the suspension mother liquor, and disperse the resulting mixed liquid as an eco-friendly dust curing agent.
[0010] As a preferred technical solution, the mass-to-volume ratio of carboxymethyl cellulose to sodium hydroxide solution in step S1 is 20-30 mg: 100 mL; the concentration of chitosan in the mixed acid solution is 2-4 wt%, and the weight ratio of chitosan to CMC-NaOH composite coagulation solution is 1:2-4.
[0011] As a preferred technical solution, the weight parts of each reaction raw material in step S3 are: bentonite: 20-38, CMC: 10-25, DMF: 10-20, HMDI: 10-20, and ferric chloride solution: 20-33.
[0012] As a preferred technical solution, the weight parts of each raw material in step S4 are as follows: antifreeze: 3-7, anionic surfactant: 3-10, superabsorbent resin: 20-30, M-carboxymethyl cellulose: 17-30, CTS-PA-CMC: 15-30, white viscous paste intermediate: 20-32.
[0013] Furthermore, the antifreeze is at least one of anhydrous ethanol, glycerol, or dipropylene glycol butyl ether; the anionic surfactant is sodium dodecylbenzenesulfonate or / and sodium dodecyl sulfate.
[0014] As a preferred technical solution, the method for preparing the carboxymethyl cellulose is as follows: water hyacinth powder is soaked in a 5-8 wt% ammonia solution for 40-45 hours, the soaked water hyacinth powder is washed and dried, and then reacted at 60-70℃ for 50-70 minutes with ethanol as solvent, sodium hydroxide as alkalizing agent and chloroacetic acid as etherifying agent.
[0015] Furthermore, the weight proportions of each raw material are as follows: water hyacinth powder: 80-120, ethanol: 40-50, sodium hydroxide: 15-25, chloroacetic acid: 23-38.
[0016] As a preferred technical solution, the superabsorbent resin is prepared by the following method: carboxymethyl cellulose, acrylic acid, and acrylamide are mixed evenly, and then sodium persulfate-sodium bisulfite initiator and N,N,N,N-tetramethylethylenediamine crosslinking agent are added. The mixture is then subjected to a water bath reaction at 55-65°C under a nitrogen atmosphere for 2-3 hours. The crude product is then placed in an ethanol solution and soaked for 8-12 hours, dried, and pulverized to obtain the water hyacinth CMC superabsorbent resin.
[0017] Furthermore, the weight proportions of each raw material are as follows: carboxymethyl cellulose: 13-25, acrylic acid: 5-17, acrylamide: 5-15, sodium persulfate-sodium bisulfite: 2-6, N,N,N,N-tetramethylethylenediamine: 3-10.
[0018] The present invention has the following advantages:
[0019] (1) The present invention uses bentonite as a filler, which can react with acidic aerosols adhering to the road surface, effectively remove harmful substances, and at the same time reduce the friction between the wheel and the road surface to a reasonable safety range, thus having a certain optimization effect on the road.
[0020] (2) The present invention uses water hyacinth as raw material to prepare water hyacinth CMC. Water hyacinth CMC can be used to prepare highly absorbent resin, which can be used as a water-retaining agent for dust curing agent. It has strong water absorption and water retention properties. Furthermore, the CMC extracted from water hyacinth is modified to make M-CMC as a binder, which not only has better adsorption and water retention capabilities, but also effectively alleviates the problem of species invasion.
[0021] (3) Common dust curing agents are unstable at high temperatures and easily decompose and lose their effectiveness, resulting in high transportation costs. The dust curing agent prepared by the method of this invention has high stability and its dust removal effect is less affected by temperature. It still has a high dust removal effect at both low and high temperatures and can be used for dust removal in the region all year round, effectively reducing dust removal costs. In addition, in this invention, carboxymethyl cellulose is combined with bentonite, so the product is rarely affected by mold. It does not need to maintain a high pH value or use preservatives during storage, which is conducive to transportation and storage and effectively reduces costs.
[0022] (4) The BT-g-CMC prepared by this invention can effectively absorb nitrogen and phosphorus compounds in water. Therefore, after being applied to the road surface, it can enter the sewer pipe or pool after being washed by rainwater, thus solving some water pollution problems. The white viscous paste intermediate can effectively adsorb and combine with organic and inorganic pollutants on urban road surfaces, which can largely solve the problems of heavy metals, microplastics and other pollutants on urban road surfaces. Detailed Implementation
[0023] The present invention will be further described below with reference to embodiments, but the scope of protection of the present invention is not limited to the following description:
[0024] In this invention: carboxymethyl cellulose is CMC, chitosan is CTS, phytic acid is PA, polyacrylamide is PAM, M-carboxymethyl cellulose is M-CMC, N,N-dimethylformamide is DMF, and dicyclohexylmethane diisocyanate is HMDI.
[0025] Example 1: A method for preparing an eco-friendly dust solidification agent includes the following steps:
[0026] S1. Preparation of CTS-PA-CMC:
[0027] (1) Preparation of carboxymethyl cellulose: 80 parts by weight of water hyacinth powder were soaked in 5 wt% ammonia solution for 40 h. After soaking, the water hyacinth powder was washed and dried. Then, it was reacted at 60 °C for 50 min with 40 parts by weight of ethanol as solvent, 15 parts by weight of sodium hydroxide as alkalizing agent and 23 parts by weight of chloroacetic acid as etherifying agent.
[0028] (2) Dissolve carboxymethyl cellulose in a 30 wt% sodium hydroxide solution to obtain a CMC-NaOH composite coagulation solution; dissolve chitosan in a mixed acid solution of phytic acid and acetic acid to remove bubbles, and slowly add it to the CMC-NaOH composite coagulation solution. Let it stand for 20 min to obtain chitosan-phytic acid-carboxymethyl cellulose CTS-PA-CMC; the mass-volume ratio of carboxymethyl cellulose to sodium hydroxide solution is 20 mg: 100 mL; the concentration of chitosan in the mixed acid solution is 2 wt%, and the weight ratio of chitosan to CMC-NaOH composite coagulation solution is 1:2;
[0029] S2.CMC modification: Separately, carboxymethyl cellulose was dissolved in a 2.8 wt% polyacrylamide solution to prepare M-carboxymethyl cellulose with a target concentration of 3 wt%.
[0030] S3. Acid leaching and crosslinking: 20 parts by weight of bentonite were acid-leached in nitric acid solution for 2 hours. After acid leaching, 10 parts by weight of CMC and 10 parts by weight of DMF were added to the bentonite, followed by 10 parts by weight of HMDI. The mixture was reacted under nitrogen protection for 6 hours to obtain BT-g-CMC. BT-g-CMC was added dropwise to 20 parts by weight of ferric chloride solution to form a hydrogel, resulting in a white viscous paste-like intermediate.
[0031] S4. Mixing:
[0032] (1) Preparation of superabsorbent resin: Take 13 parts by weight of carboxymethyl cellulose prepared in step S1, 5 parts by weight of acrylic acid, and 5 parts by weight of acrylamide, mix them evenly, add 2 parts by weight of initiator sodium persulfate-sodium bisulfite, and 3 parts by weight of crosslinking agent N,N,N,N-tetramethylethylenediamine, and carry out water bath reaction at 55°C under nitrogen atmosphere for 2 hours; place the crude product in ethanol solution, soak for 8 hours, dry and pulverize, and finally obtain water hyacinth CMC superabsorbent resin.
[0033] (2) Mix and stir 3 parts by weight of antifreeze, 3 parts by weight of anionic surfactant and 20 parts by weight of superabsorbent resin, then add 17 parts by weight of M-carboxymethyl cellulose prepared in step S2 and disperse evenly to obtain a suspension mother liquor; add 15 parts by weight of CTS-PA-CMC prepared in step S1 and 20 parts by weight of white viscous paste intermediate prepared in step S3 to the suspension mother liquor, and disperse the resulting mixed liquid as an eco-friendly dust curing agent; wherein, the antifreeze is anhydrous ethanol; and the anionic surfactant is sodium dodecylbenzenesulfonate.
[0034] Example 2: A method for preparing an eco-friendly dust solidification agent includes the following steps:
[0035] S1. Preparation of CTS-PA-CMC:
[0036] (1) Preparation of carboxymethyl cellulose: 120 parts by weight of water hyacinth powder were soaked in 8 wt% ammonia solution for 45 h. After soaking, the water hyacinth powder was washed and dried. Then, it was reacted at 70 °C for 70 min with 50 parts by weight of ethanol as solvent, 25 parts by weight of sodium hydroxide as alkalizing agent and 38 parts by weight of chloroacetic acid as etherifying agent.
[0037] (2) Carboxymethyl cellulose was dissolved in a 45 wt% sodium hydroxide solution to obtain a CMC-NaOH composite coagulation solution; chitosan was dissolved in a mixed acid solution of phytic acid and acetic acid to remove bubbles, and then slowly added to the CMC-NaOH composite coagulation solution. After standing for 40 min, chitosan-phytic acid-carboxymethyl cellulose CTS-PA-CMC was obtained; the mass-volume ratio of carboxymethyl cellulose to sodium hydroxide solution was 30 mg: 100 mL; the concentration of chitosan in the mixed acid solution was 4 wt%, and the weight ratio of chitosan to CMC-NaOH composite coagulation solution was 1:4;
[0038] S2.CMC modification: Separately, carboxymethyl cellulose was dissolved in a 4 wt% polyacrylamide solution to prepare M-carboxymethyl cellulose with a target concentration of 4 wt%.
[0039] S3. Acid leaching and crosslinking: 38 parts by weight of bentonite were acid-leached in nitric acid solution for 3 hours. After acid leaching, 25 parts by weight of CMC and 20 parts by weight of DMF were added to the bentonite, followed by 20 parts by weight of HMDI. The mixture was reacted under nitrogen protection for 9 hours to obtain BT-g-CMC. BT-g-CMC was added dropwise to 33 parts by weight of ferric chloride solution to form a hydrogel, resulting in a white viscous paste-like intermediate.
[0040] S4. Mixing:
[0041] (1) Preparation of super absorbent resin: Take 25 parts by weight of carboxymethyl cellulose prepared in step S1, 17 parts by weight of acrylic acid, and 15 parts by weight of acrylamide, mix them evenly, add 6 parts by weight of initiator sodium persulfate-sodium bisulfite, and 10 parts by weight of crosslinking agent N,N,N,N-tetramethylethylenediamine, and carry out water bath reaction at 65°C under nitrogen atmosphere for 3 hours; place the crude product in ethanol solution, soak for 12 hours, dry and pulverize, and finally obtain water hyacinth CMC super absorbent resin;
[0042] (2) After mixing and stirring 7 parts by weight of antifreeze, 10 parts by weight of anionic surfactant and 30 parts by weight of superabsorbent resin, add 30 parts by weight of M-carboxymethyl cellulose prepared in step S2 and disperse evenly to obtain a suspension mother liquor; add 30 parts by weight of CTS-PA-CMC prepared in step S1 and 32 parts by weight of white viscous paste intermediate prepared in step S3 to the suspension mother liquor, and disperse the resulting mixed liquid as an eco-friendly dust curing agent; wherein, the antifreeze is a mixture of anhydrous ethanol and dipropylene glycol butyl ether; and the anionic surfactant is sodium dodecyl sulfate.
[0043] Example 3: A method for preparing an eco-friendly dust solidification agent includes the following steps:
[0044] S1. Preparation of CTS-PA-CMC:
[0045] (1) Preparation of carboxymethyl cellulose: 95 parts by weight of water hyacinth powder were soaked in 6 wt% ammonia solution for 42 h. After soaking, the water hyacinth powder was washed and dried. Then, it was reacted at 63 °C for 52 min with 43 parts by weight of ethanol as solvent, 18 parts by weight of sodium hydroxide as alkalizing agent and 25 parts by weight of chloroacetic acid as etherifying agent.
[0046] (2) Carboxymethyl cellulose was dissolved in a 36 wt% sodium hydroxide solution to obtain a CMC-NaOH composite coagulation solution; chitosan was dissolved in a mixed acid solution of phytic acid and acetic acid to remove bubbles, and then slowly added to the CMC-NaOH composite coagulation solution. After standing for 28 min, chitosan-phytic acid-carboxymethyl cellulose CTS-PA-CMC was obtained; the mass-volume ratio of carboxymethyl cellulose to sodium hydroxide solution was 22 mg:100 mL; the concentration of chitosan in the mixed acid solution was 2.5 wt%, and the weight ratio of chitosan to CMC-NaOH composite coagulation solution was 1:3;
[0047] S2.CMC modification: Separately, carboxymethyl cellulose was dissolved in a 3 wt% polyacrylamide solution to prepare M-carboxymethyl cellulose with a target concentration of 3.2 wt%.
[0048] S3. Acid leaching and crosslinking: 25 parts by weight of bentonite were acid-leached in nitric acid solution for 2.5 h. After acid leaching, 18 parts by weight of CMC and 14 parts by weight of DMF were added to the bentonite, followed by 12 parts by weight of HMDI. The reaction was carried out under nitrogen protection for 7 h to obtain BT-g-CMC. BT-g-CMC was added dropwise to 25 parts by weight of ferric chloride solution to form a hydrogel, resulting in a white viscous paste-like intermediate.
[0049] S4. Mixing:
[0050] (1) Preparation of superabsorbent resin: Take 18 parts by weight of carboxymethyl cellulose prepared in step S1, 10 parts by weight of acrylic acid, 10 parts by weight of acrylamide, mix them evenly, add 3 parts by weight of initiator sodium persulfate-sodium bisulfite, and 5 parts by weight of crosslinking agent N,N,N,N-tetramethylethylenediamine, and carry out water bath reaction at 58°C under nitrogen atmosphere for 2.4 h; place the crude product in ethanol solution, soak for 9.5 h, dry and pulverize, and finally obtain water hyacinth CMC superabsorbent resin;
[0051] (2) After mixing and stirring 4 parts by weight of antifreeze, 5 parts by weight of anionic surfactant and 24 parts by weight of superabsorbent resin, add 22 parts by weight of M-carboxymethyl cellulose prepared in step S2 and disperse evenly to obtain a suspension mother liquor; add 20 parts by weight of CTS-PA-CMC prepared in step S1 and 26 parts by weight of white viscous paste intermediate prepared in step S3 to the suspension mother liquor, and the resulting mixed liquid is an eco-friendly dust curing agent; wherein, the antifreeze is a mixture of anhydrous ethanol, glycerol and dipropylene glycol butyl ether; the anionic surfactant is a mixture of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate.
[0052] Example 4: A method for preparing an eco-friendly dust solidification agent includes the following steps:
[0053] S1. Preparation of CTS-PA-CMC:
[0054] (1) Preparation of carboxymethyl cellulose: 110 parts by weight of water hyacinth powder were soaked in 7 wt% ammonia solution for 44 h. After soaking, the water hyacinth powder was washed and dried. Then, it was reacted at 68 °C for 65 min with 48 parts by weight of ethanol as solvent, 22 parts by weight of sodium hydroxide as alkalizing agent and 33 parts by weight of chloroacetic acid as etherifying agent.
[0055] (2) Carboxymethyl cellulose was dissolved in a 40 wt% sodium hydroxide solution to obtain a CMC-NaOH composite coagulation solution; chitosan was dissolved in a mixed acid solution of phytic acid and acetic acid to remove bubbles, and then slowly added to the CMC-NaOH composite coagulation solution. After standing for 35 min, chitosan-phytic acid-carboxymethyl cellulose CTS-PA-CMC was obtained; the mass-volume ratio of carboxymethyl cellulose to sodium hydroxide solution was 28 mg:100 mL; the concentration of chitosan in the mixed acid solution was 3.5 wt%, and the weight ratio of chitosan to CMC-NaOH composite coagulation solution was 1:3.5;
[0056] S2.CMC modification: Separately, carboxymethyl cellulose was dissolved in a 3.8 wt% polyacrylamide solution to prepare M-carboxymethyl cellulose with a target concentration of 3.6 wt%.
[0057] S3. Acid leaching and crosslinking: 20-38 parts by weight of bentonite were acid-leached in nitric acid solution for 2.8 h. After acid leaching, 22 parts by weight of CMC and 18 parts by weight of DMF were added to the bentonite, followed by 16 parts by weight of HMDI. The reaction was carried out under nitrogen protection for 8 h to obtain BT-g-CMC. BT-g-CMC was added dropwise to 30 parts by weight of ferric chloride solution to form a hydrogel, resulting in a white viscous paste-like intermediate.
[0058] S4. Mixing:
[0059] (1) Preparation of superabsorbent resin: Take 22 parts by weight of carboxymethyl cellulose prepared in step S1, 15 parts by weight of acrylic acid, and 12 parts by weight of acrylamide, mix them evenly, add 5 parts by weight of initiator sodium persulfate-sodium bisulfite, and 8 parts by weight of crosslinking agent N,N,N,N-tetramethylethylenediamine, and carry out water bath reaction at 62°C under nitrogen atmosphere for 2.8 h; place the crude product in ethanol solution, soak for 11 h, dry and pulverize, and finally obtain water hyacinth CMC superabsorbent resin.
[0060] (2) After mixing and stirring 6 parts by weight of antifreeze, 8 parts by weight of anionic surfactant and 27 parts by weight of superabsorbent resin, add 25 parts by weight of M-carboxymethyl cellulose prepared in step S2 and disperse evenly to obtain a suspension mother liquor; add 25 parts by weight of CTS-PA-CMC prepared in step S1 and 30 parts by weight of white viscous paste intermediate prepared in step S3 to the suspension mother liquor, and disperse the resulting mixed liquid as an eco-friendly dust curing agent; wherein, the antifreeze is dipropylene glycol butyl ether; and the anionic surfactant is a mixture of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate.
[0061] Superabsorbent polymer (SAP) of water hyacinth was prepared by processing water hyacinth CMC. The thermal weight loss of this superabsorbent polymer exhibited three stages: the first stage (30-200℃) involved residual adsorbed and bound water in the resin, with a weight loss rate of 13.12%; the second stage (200-354℃) resulted in a weight loss rate of 28.11%, due to the decomposition of oligomers and polymers within the resin; and the third stage (354-447℃) resulted in a weight loss rate of 46.02%, due to further polymer decomposition. This demonstrates that the superabsorbent polymer (SAP) of water hyacinth possesses certain high-temperature resistance and can be used under high-temperature conditions.
[0062] Sodium carboxymethyl cellulose is reacted with chitosan and phytic acid to form a chitosan-phytic acid-sodium carboxymethyl cellulose composite gel. This gel can adsorb most heavy metals such as Cu, Cr, Zn, and Pb from road surfaces, as well as inorganic pollutants such as microplastics. This property is not found in commonly used dust suppressants on the market. The addition of the chitosan-phytic acid-sodium carboxymethyl cellulose composite gel can greatly improve the ability to adsorb heavy metals and microplastics from road surfaces, and can solidify them inside the gel, resulting in a long-lasting protective effect.
[0063] The following experiments illustrate the beneficial effects of this invention:
[0064] 1. The eco-friendly dust curing agents prepared in Examples 1-4 were loaded into a spraying device and sprayed on urban roads. Conventional methods were used to test various relevant parameters. The experimental data are shown in Table 1.
[0065] Table 1: Experimental Results of Dust Suppression Effect
[0066] As can be seen from Table 1, the dust suppressant provided by the present invention has excellent dust suppression effect, low carbon steel corrosion rate, no corrosive effect on vehicles, and can achieve the same technical effect as adding corrosion inhibitors even without adding inorganic salt corrosion inhibitors. It will not affect road traffic conditions, will not harm animals and plants, is safe and environmentally friendly, and can keep the road dust-free for more than fourteen days.
[0067] 2. Dust suppression efficiency test
[0068] The testing method is as follows: Select soil samples from Chengdu urban roads with a mesh size of 10 or smaller, and dry them in an oven at 80℃ for 180 minutes to remove moisture. Then, place the samples in two petri dishes, ensuring the sample surface is flush with the dish surface. Spray a dust hardener (3L / m²) into each petri dish. 2 After drying in an oven at 80℃ for 180 minutes, each sample was weighed, with the mass of the sample being ω1. Then, each sample was placed in a wind tunnel and subjected to erosion at a surface wind speed of 30 m / s for 5 minutes. Afterward, each sample was weighed, with the mass of the remaining sample being ω2. The erosion rate was calculated using the following formula:
[0069]
[0070] Where E is the wind erosion rate of the sample; w1 is the mass of the soil sample before erosion; and w2 is the mass of the soil sample after erosion. The wind erosion rate of sample 1 is E1, and the wind erosion rate of sample 2 is E2. Their average value is taken as E. Then, the dust suppression efficiency = 1 - E;
[0071] The experimental results are shown in Table 2:
[0072] Table 2: Experimental Results of Dust Suppression Efficiency
[0073] Table 2 shows that when the dust solidifier containing modified carboxymethyl cellulose (M-CMC) is applied to urban roads in Chengdu, after a period of time, it is evident that the dust solidifier can bind dust particles, effectively solidifying the dust and significantly improving dust suppression efficiency. Furthermore, comparative analysis with other commonly used dust suppressants on the market shows that the addition of M-CMC significantly improves the water retention and water stability of the solidified dust, and increases the external force required to break up dust agglomerates, thus enhancing water stability.
[0074] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, are covered within the scope of protection of the present invention.
Claims
1. A method for preparing an eco-friendly dust solidification agent, characterized in that, Includes the following steps: S1. Preparation of CTS-PA-CMC: Carboxymethyl cellulose is dissolved in a 30-45 wt% sodium hydroxide solution to obtain a CMC-NaOH composite coagulation solution; chitosan is dissolved in a mixed acid solution of phytic acid and acetic acid to remove bubbles, and is slowly added to the CMC-NaOH composite coagulation solution. After standing for 20-40 min, chitosan-phytic acid-carboxymethyl cellulose CTS-PA-CMC is obtained. S2.CMC modification: Separately, carboxymethyl cellulose is dissolved in a 2.8-4 wt% polyacrylamide solution to prepare M-carboxymethyl cellulose with a target concentration of 3-4 wt%. S3. Acid leaching and crosslinking: Bentonite is acid-leached in nitric acid solution for 2-3 hours. After acid leaching, CMC and DMF are added to the bentonite, followed by HMDI. The reaction is carried out under nitrogen protection for 6-9 hours to obtain BT-g-CMC. BT-g-CMC is added dropwise to ferric chloride solution to form a hydrogel, resulting in a white viscous paste-like intermediate. S4. Mixing: After mixing and stirring the antifreeze, anionic surfactant, and superabsorbent resin, add the M-carboxymethyl cellulose prepared in step S2 and disperse evenly to obtain a suspension mother liquor; add the CTS-PA-CMC prepared in step S1 and the white viscous paste intermediate prepared in step S3 to the suspension mother liquor, and disperse the resulting mixed liquid as an eco-friendly dust curing agent; wherein, the weight parts of each raw material are: antifreeze: 3-7, anionic surfactant: 3-10, superabsorbent resin: 20-30, M-carboxymethyl cellulose: 17-30, CTS-PA-CMC: 15-30, white viscous paste intermediate: 20-32.
2. The preparation method of the eco-friendly dust solidification agent according to claim 1, characterized in that, In step S1, the mass-to-volume ratio of carboxymethyl cellulose to sodium hydroxide solution is 20-30 mg: 100 mL; the concentration of chitosan in the mixed acid solution is 2-4 wt%, and the weight ratio of chitosan to CMC-NaOH composite coagulation solution is 1:2-4.
3. The preparation method of the eco-friendly dust solidification agent according to claim 1, characterized in that, The weight parts of each reaction raw material in step S3 are: bentonite: 20-38, CMC: 10-25, DMF: 10-20, HMDI: 10-20, ferric chloride solution: 20-33.
4. The preparation method of the eco-friendly dust solidification agent according to claim 1, characterized in that, The antifreeze is at least one of anhydrous ethanol, glycerol, or dipropylene glycol butyl ether; the anionic surfactant is sodium dodecylbenzene sulfonate or / and sodium dodecyl sulfate.
5. The preparation method of the eco-friendly dust solidification agent according to claim 1, characterized in that, The method for preparing the carboxymethyl cellulose is as follows: water hyacinth powder is soaked in a 5-8 wt% ammonia solution for 40-45 hours, the soaked water hyacinth powder is washed and dried, and then reacted at 60-70℃ for 50-70 minutes with ethanol as solvent, sodium hydroxide as alkalizing agent and chloroacetic acid as etherifying agent.
6. The preparation method of the eco-friendly dust solidification agent according to claim 5, characterized in that, The weight parts of each raw material are as follows: water hyacinth powder: 80-12, ethanol: 40-50, sodium hydroxide: 15-25, chloroacetic acid: 23-38.
7. The preparation method of the eco-friendly dust solidification agent according to claim 1, characterized in that, The superabsorbent resin is prepared by the following method: carboxymethyl cellulose, acrylic acid, and acrylamide are mixed evenly, and then sodium persulfate-sodium bisulfite initiator and N,N,N,N-tetramethylethylenediamine crosslinking agent are added. The mixture is then subjected to a water bath reaction at 55-65°C under a nitrogen atmosphere for 2-3 hours. The crude product is then placed in an ethanol solution and soaked for 8-12 hours, dried, and pulverized to obtain the water hyacinth CMC superabsorbent resin.
8. The preparation method of the eco-friendly dust solidification agent according to claim 7, characterized in that, The weight parts of each raw material are as follows: carboxymethyl cellulose: 13-25, acrylic acid: 5-17, acrylamide: 5-15, sodium persulfate-sodium bisulfite: 2-6, N,N,N,N-tetramethylethylenediamine: 3-10.
Citation Information
Patent Citations
Colorful environment-friendly dust suppressant and preparation and use methods thereof
CN106928901A
Preparation method of waterproof-type coal dust depressor
CN108570308A
Environmentally-friendly multifunctional dust suppressant and preparation method thereof
CN103059347A
Environment-friendly dust suppressant and preparation method thereof
CN111349421A